Coursework in industrial doctorates: a worthwhile contribution to students’ training? - Sin, Cristina (2020)
The integration of coursework in doctoral programmes is becoming increasingly common worldwide. In Portugal, too, coursework is now part of many doctorates and is usually assigned to the first year. This paper aims to understand if coursework is also an element of the relatively recent industrial doctorates in Portugal and, in this case, if it represents an added value for the training and experience of doctoral candidates in a primarily research-based degree, but driven by the shared interests of industry and academia. The perceptions of students enrolled in industrial doctorates were gathered through focus groups. Findings suggest that students tend to believe that compulsory coursework does not add much value to their training, although its relevance seems to increase when students are given the possibility of choosing courses which are related to their research topic or when courses have a practical orientation. These findings invite a reconsideration of curriculum design in doctoral degrees in the direction of increased flexibility and more personalised learning plans.